The great demand depression - Mark Weder (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
This paper entertains the notion that disturbances on the demand side play a central role in our understanding of the Great Depression. In fact, from Euler equation residuals we are able to identify a series of unusually large negative demand shocks that appeared to have hit the U. S. economy during the 1930s. This echoes the view originally promoted by Temin (1976). We apply these measured demand shocks to a dynamic general equilibrium model and find that size and sequence of shocks can generate a pattern of the model economy that is not unlike data. The model is able to account for the lion's share of the decline in economic activity and is able to exaggerate realistic persistence.
urn:nbn:de:kobv:11-10050068
Keywords: E32; 330; Great Depression; Dynamic General Equilibrium; Demand Shocks